Estudo de impacto de vizinhança e licenciamento urbanístico-ambiental : desafios e inovações - Tomanik, Raquel (2008)
The Neighborhood Impact Study (NIS), urban instrument introduced by the Status of the City Federal Law nº. 10.257 of 2001 , has been studied in this work so as to verify its applicability in integrated licensing procedures. We have sought to establish relations of affinity and complementation between NIS and other instruments in support to the territorial planning and management, based on the review of bibliographic concepts and methods in analysis and evaluation of urban and environmental impacts. Then we have traced the NIS path, from founding principles, such as the concern to minimize hassles from building in surrounding lots, until its consolidation as a tool of mitigation and compensation of the negative reflexes of the urban development. The analysis of the implementation processes in Araraquara e Santo André has enabled the verification of the potentialities and problems of the application of NIS in integrated urban-environmental licensing, noting some guidelines for regulating of the instrument in other locations.